PEMBERDAYAAN GENERASI MUDA DALAM OPTIMALISASI DISTRIBUSI DAN PENGELOLAAN KEPEMIMPINAN DIRI DI DESA CURAHREJO CANGKRING JEMBER - Akhmad Dzukaul Fuad (Dedication : Jurnal Pengabdian Masyarakat, 2018)
This article aims to provide an alternative solution in empowering and developing human resources in Cangkor Jangkgawah Cangkor Jangkgawah Village. Based on situation analysis, the potential of young generation in Curahrejo village is not maximally utilized for institutional institutional development of mosque as center of socio-cultural activity of society. Alternative solutions offered in this article include self-leadership training for young people who are members of youth mosque (REMAS) al Ikhlas, the training is packaged in the form of Islamic leadership tutorials, organizational governance, social problem solving practices. The ultimate goal of the tutorial and advisory program is to inspire the instinct of leadership and governance of REMAS al Ikhlas organization for empowerment of mosque potency as center of social culture activity of Cangkor Village Curahrejo Village.